AB0833 An Internet Survey of Common Treatments Used by Patients with Gout. (10th June 2014) - Singh, J.A.; Bharat, A.; Edwards, L.
Abstract : Background: Little is known about patients with gout with regards to the use of complimenatry and non-pharmacological approaches to treatment of gout. Qualitative work has shown that patients are interested in these treatment options. To our knowledge, there are no other studies of characteristics of patients who use supplements for gout. Objectives: To assess the frequency of use of urate-lowering therapy (ULT) and natural supplements including cherry extract by patients with gout. Methods: A pop-up on the website the Gout and Uric Acid Education Society's website (http://gouteducation.org ) informed people about the optional survey from 11/20/2013 to 01/15/14. The survey queried people regarding the use of ULT and supplements. Results: Of the 162 survey respondents, 121 (74%) reported gout. Mean age of survey responders was 55.4 years (standard deviation, 14.5), 69% were men and 71% were White. Gout disease duration was ≤1 year in 29%, 1-5 years in 22%, 5-10 years in 22% and >10 years in 21% (missing, 6%). Gout flares were common, with 89% with ≥1 gout flare in the last month (i.e. >3/year). 51% had been prescribed allopurinol of febuxostat, 78% missed it for <7 days/month. 42% participants were taking cherry extract or juice and 21% were taking other natural supplements. Conclusions: Use of cherry extract and natural supplements is not uncommon in patients with gout. Only half of all gout patients were prescribed ULT by their providers. Acknowledgements: We thanks gouteducation.org for displaying our survey. Disclosure of Interest: J. Singh Grant/research support: Takeda, Savient, Consultant for: Takeda, Savient, Novartis, Allergan, Regeneron, A. Bharat: None declared, L. Edwards: None declared DOI: 10.1136/annrheumdis-2014-eular.4846